Uniform thickness control without pre-specifying the length scale target under the level set topology optimization framework. (January 2018) - Liu, Jikai; Li, Lei; Ma, Yongsheng
Highlights: Realizes the uniform thickness/diameter topology design under the level set topology optimization framework. Reuses the previously developed length scale control functional but provides a more accurate sensitivity calculation. Develops a modified version of the length scale control functional which eliminates the need of pre-specifying the length scale target. Performs numerical case study on both 2D and 3D examples. Abstract: In the authors' earlier work[1], a component length scale control functional was proposed to regulate the topology evolution with uniform thickness distribution; however, the sensitivity result was numerically calculated with certain approximation. In order to make this functional better work for complex design problems, the sensitivity result is now analytically calculated with the aid of the structural skeleton-based non-signed distance level set field. More importantly, this component length scale control functional has been upgraded to eliminate the need of pre-specifying the length scale target. By using control functional instead of constraints, a benefit is that the structural performance and length scale control effect can be balanced by the weight factor, because it is not always necessary to strictly achieve the uniform thickness distribution while drastically compromising the structural performance. Therefore, this work studies the uniform thickness control in a multi-objective manner. Effectiveness of the proposed method is proved through a few 2D and 3D numerical case studies.